Thermodynamic and kinetic studies of heavy metal adsorption by modified nano-zeolite. Issue 2 (4th March 2021) - Kamran Haghighi, Hossein; Irannajad, Mehdi; MohammadJafari, Alireza
ABSTRACT: In this study, for the first time, nano-sized clinoptilolite zeolite produced by a dry planetary ball mill in the presence of sodium hexametaphosphate was employed to remove heavy metals. Results represented that the concentration of adsorbed ions on nano-zeolite increases with increasing pH, initial concentration of metals, and temperature. The maximum adsorption efficiency for Ni 2+, Cd 2+, and Cu 2+ was found to be 74.20%, 97.60%, and 99.50% at a pH of 7.5 and 60°C, respectively. The adsorption of Ni 2+, Cd 2+ and Cu 2+ on nano-zeolite increased from 44.40% to 74.20 %, 76.4% to 97.60%, and 94.30% to 99.50% by enhancing temperature from 20 to 60 °C. Furthermore, Gibbs's free energy obtained from thermodynamic evaluations depicted that adsorptions had spontaneous behavior. According to Langmuir models, the maximum capacity (qm ) of Ni 2+, Cu 2+, and Cd 2+ using nano-zeolite was found to be 17.79, 17.92, and 18.32 mg/g. Adsorption isotherms showed that results fitted better on the Langmuir model for Ni 2+ and Cu 2+ and the Freundlich model for Cd +2 because the correlation coefficients (R 2 ) were 0.99 for them. Finally, the pseudo-second-order kinetic model was selected to interpret the experimental data.